The export additionality of innovation policy. (25th January 2019) - Freel, Mark; Liu, Rebecca; Rammer, Christian
Abstract: The empirical evidence that innovation policies often lead to innovation additionality is long-standing. However, innovation is an intermediate outcome. Innovations are important to the extent that they contribute to some broader goal, such as the competitiveness of firms and economies. To this end, we take exporting as an important indicator of competitiveness and investigate whether innovation interventions lead to exporting outcomes. Using the Mannheim Innovation Panel, the current study explores whether innovation interventions at various administrative levels associate with changing export behaviors among German Small- and Medium-sized Enterprise (SMEs). Our results provide evidence of the scope for policymakers to employ innovation interventions as export policy.